Policy–governance–culture dynamics in Myanmar education reform: implications for transformational leadership practice - Chi Che; Win Pa Pa Tun (International Journal of Evaluation and Research in Education (IJERE), 2026)
Myanmar’s education reform faces a persistent enactment gap because policy intent is filtered through governance feasibility and culturally grounded legitimacy norms. This study examined whether transformational leadership functions as a mediation practice that buffers policy–governance misalignment and under what conditions that buffering is stronger. The novelty of this study lies in proposing and testing an integrated policy–governance–culture (PGC) leadership mediation model that explains reform enactment through the joint effects of structural misalignment, leadership buffering, and culturally conditioned legitimacy. An explanatory sequential mixed-methods design combined a two-wave time-lag survey of teachers and middle leaders from 48 schools (N=720) with semi-structured interviews to clarify mechanisms. Measurement models showed acceptable-to-strong fit (CFA: CFI=0.956, TLI=0.948, RMSEA=0.044, SRMR=0.041). Multilevel SEM (ICC_RE=0.11) indicated that policy–governance misalignment directly reduced reform enactment (β=−0.15, p=.003) while increasing leadership mediation practices (β=0.25, p